Między konwencją a inwencją. Osobliwości językowe w listach abpa Adama Sapiehy skierowanych do prymasa Augusta Hlonda - Sieradzka, Paulina (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2018)
In this text the stylistic features of Polish letters of Archbishop Adam Sapieha addressed to the Primate August Hlond. To these letters, the author arrived, by inquiring in Archdiocesan Archives in Gniezno. The relevant subject of the article is five puzzling expressions in terms of usage, meaning and construction. The first example: a coterie is a single lex, the other four: real rape, journalistic nerve, thick gloves and operettas performances are constant expressions. As demonstrated by the analysis of the occurence of words and the analysis of expressions, the word coterie reveals the pejorative relation of the speaker to the circumstances described. The expression of real rape is an idiolectic metaphor and the expression of journalistic nerve is a phraseological modification. The phrase to put thick gloves as well as the expression of operetta performances are contaminations. They prove the existence of Sapieha’s individual language and the efforts of the sender of the letters to make the word and its meaning as complete as possible.